Fractionated carbon ion irradiations of the rat spinal cord: comparison of the relative biological effectiveness with predictions of the local effect model - Saager, Maria; Glowa, Christin; Peschke, Peter; Brons, Stephan; Grün, Rebecca; Scholz, Michael; Debus, Jürgen; Karger, Christian (Radiation oncology, 2020)
To determine the relative biological effectiveness (RBE) and α/β-values after fractionated carbon ion irradiations of the rat spinal cord with varying linear energy transfer (LET) to benchmark RBE-model calculations.
Gesehen am 02.04.2020